2020
DOI: 10.1186/s12891-020-03210-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the responsiveness of the WOMAC and the 12-item WHODAS 2.0 in patients with Kashin–Beck disease

Abstract: Background: Several questionnaires have been used to assess the health status of patients with Kashin-Beck disease (KBD) in clinical trials, but the evidence regarding the responsiveness of these instruments in KBD patients is limited. Therefore, the aim of this study was to evaluate and compare the responsiveness of the Chinese version of the Western Ontario and McMaster Universities Osteoarthritis index (WOMAC) and 12-item World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) in KBD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Comparing KBDQOL with SF-36, some aspects are unique to KBDQOL (for example, social support, economics, etc.). Among the 12 physical function and activity limitation items of KBDQOL, only 66% and 50% respectively are part of the WOMAC and Lequesne indexes, respectively [18]. During the personal interview, more than 40% of the patients put forward two new contents as follow: Q2.2, in the past 30 days, "How many days do you need to take painkillers?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing KBDQOL with SF-36, some aspects are unique to KBDQOL (for example, social support, economics, etc.). Among the 12 physical function and activity limitation items of KBDQOL, only 66% and 50% respectively are part of the WOMAC and Lequesne indexes, respectively [18]. During the personal interview, more than 40% of the patients put forward two new contents as follow: Q2.2, in the past 30 days, "How many days do you need to take painkillers?"…”
Section: Discussionmentioning
confidence: 99%
“…KBDQOL is a low-educated KBD population survey that can be easily used in rural areas, and most of the questions are direct statements from KBD patients [9]. Some studies [16][17][18] reported the symptoms and signs of KBD, but none of the studies linked the clinical manifestations of KBD to patients' disability, restriction of daily activities, the impact of disease on income, and the impact of disease on mood. We found that KBD patients do often have restricted activities, nancial di culties, and negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…KBD remains endemic in 379 counties of 13 provinces or autonomous regions, and an estimated 37.2 million people are at high risk of developing KBD. Of these, there are 54 KBD counties in Tibet, accounting for 15.47% (National Health Commission of the People’ Republic of China, 2018; L. Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…KBD remains endemic in 379 counties of 13 provinces or autonomous regions, and an estimated 37.2 million people are at high risk of developing KBD. Of these, there are 54 KBD counties in Tibet, accounting for 15.47% (National Health Commission of the People' Republic of China, 2018; L. Yang et al, 2020). The clinical features of the disease include tuberosity of the fingers and brachydactylia, deformed and enlarged joints, and limited motion of the joints (Guo et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%